2022
DOI: 10.23958/ijirms/vol07-i07/1443
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency and the Associated Risk Factors in Adults with Thyroid Nodule in Royal Commission Hospital, Kingdom of Saudi Arabia

Abstract: Vitamin D is an essential nutrient for the human body. Its deficiency is linked with many common chronic diseases, types of cancer and thyroid disorders. Recent data have shown high rates of vitamin D deficiency, thyroid nodules and an increase in the incidence of thyroid cancer in the Kingdom of Saudi Arabia (KSA). We conducted this study to evaluate the rates of vitamin D deficiency and associated risk factors in patients with thyroid nodules in the Eastern Region of the KSA. Methods: A retrospective study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…This may be explained by the influence of Dio2, the enzyme responsible for the conversion of T4 to T3 [ 40 ], which is associated with an increased risk of increased insulin resistance and T2DM [ 39 ]. The results of the present study are in accordance with the outcomes of many studies that have shown no significant associations between DM and other associated predictors (gender, FT4, TSH, thyroid status, hematological indices, vitamin D levels and the ACR TI-RADS scoring system) [ 38 , 58 - 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…This may be explained by the influence of Dio2, the enzyme responsible for the conversion of T4 to T3 [ 40 ], which is associated with an increased risk of increased insulin resistance and T2DM [ 39 ]. The results of the present study are in accordance with the outcomes of many studies that have shown no significant associations between DM and other associated predictors (gender, FT4, TSH, thyroid status, hematological indices, vitamin D levels and the ACR TI-RADS scoring system) [ 38 , 58 - 60 ].…”
Section: Discussionsupporting
confidence: 92%